Mitochondrial DNA phylogeography of the Norway rat. - Ying Song; Zhenjiang Lan; Michael H Kohn (PLoS ONE)
Central Eastern Asia, foremost the area bordering northern China and Mongolia, has been thought to be the geographic region where Norway rats (Rattus norvegicus) have originated. However recent fossil analyses pointed to their origin in southern China. Moreover, whereas analyses of fossils dated the species' origin as ∼ 1.2-1.6 million years ago (Mya), molecular analyses yielded ∼ 0.5-2.9 Mya. Here, to study the geographic origin of the Norway rat and its spread across the globe we analyzed new and all published mitochondrial DNA cytochrome-b (cyt-b; N = 156) and D-loop (N = 212) sequences representing wild rats from four continents and select inbred strains. Our results are consistent with an origin of the Norway rat in southern China ∼ 1.3 Mya, subsequent prehistoric differentiation and spread in China and Asia from an initially weakly structured ancestral population, followed by further spread and differentiation across the globe during historic times. The recent spreading occurred mostly from derived European populations rather than from archaic Asian populations. We trace laboratory strains to wild lineages from Europe and North America and these represent a subset of the diversity of the rat; leaving Asian lineages largely untapped as a resource for biomedical models. By studying rats from Europe we made the observation that mtDNA diversity cannot be interpreted without consideration of pest control and, possibly, the evolution of rodenticide resistance. However, demographic models explored by forward-time simulations cannot fully explain the low mtDNA diversity of European rats and lack of haplotype sharing with their source from Asia. Comprehensive nuclear marker analyses of a larger sample of Norway rats representing the world are needed to better resolve the evolutionary history of wild rats and of laboratory rats, as well as to better understand the evolution of anticoagulant resistance.